Persepsi Bermukim Masyarakat Antar Generasi di Kampung Sendang Indah, Kota Semarang - Marina, Yan; Manaf, Asnawi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
As we know, relocation is one kind of alternative solution to pull squatters problem out which are unsuitable for urban. Relocation is not only to move a place to stay society to the new better place, but for the independency for that society itself. Relocation is a prosses to make that society’s life to be suitable and capable in the new settlement. Relocation which carried out all the Kali Semarang to Kampung Sendang Indah Semarang in the end of 1980 be used as the background to see how far the relocation program has been done can give an impact to the society’s alteration either directly or indirectly. Analization thecnic which used are description analysis, qualitative analysis and quantitative analysis by grouping bassed on the certain criteria by using crosstab analysis thecnic. Research was doing by interviewing the society concerning the extent changes that happen either physical aspects and socio-economic. Research was doing by interviewing the respondent from 3 generations that are staying in the Kampung Sendang Indah. Each generations seen on the development of the public life in the relocation from 3 generations. The research’s result is a comparison from the characteristics of socio-economical society Kampung Sendang Indah whom are stayed for 3 decade in the relocation seen by society mobility toward their move preferences. Their move preferences can be used as the reference changes in the socio-economic community itself.